A gestão pública em São José dos Campos no biênio 2013-2014: licitações e gerenciamento de obras - Paula, Décio Fernando Barbosa de (2014)
The bidding process of PMSJC follow all norms and rules making the law as its guiding 8666 1993 aiming to speak of the creation of permanent Commission in bids for engineering works and services of the Department of Public Works created on November 1, 2013 through of decree No. 2693/2013. This committee aims to open bids from the preparation of notices until the completion of the signing of the contract by the municipality contracted by touching the objects in the Construction and Engineering Services. The committee consists of four members and four career employees who work directly for the commission to give more speed to the bidding of the prefecture and make your best management until the signing of the contract. Mode of Competitive Bidding will be addressed in order to explain this type of modality in procurement of Works and Engineering Services. During the studies of this paper the reader will be able to identify the goals of this thesis were achieved data analysis that resulted in the deployment and the permanence of the Committees on Bids decentralized operationalization of bids in terms of price and Public Decision-Competition converged improvement in outcomes of organizational administrative processor, with its continuity achieved great success in efficiently and effectively, and public management with the significant decrease in the time of the bidding process until the contract is signed making this right form the government's strategy to create a commission to specify Works and Engineering Services.